Avatar, the last airbender. Katara and the pirate's silver - Hicks, Faith Erin (Dark Horse Books, 2020)
"When Team Avatar is suddenly ambushed by the Fire Nation, Katara gets separated from the group. Unable to rendezvous with Aang, Toph, and Sokka, Katara must avoid capture by aligning herself with some unlikely allies! The normally sweet and sensitive Katara will need to explore her tougher side if she's going to reunite with the rest of Team Avatar.... "--Provided by publisher.